2014
DOI: 10.1002/pbc.25281
|View full text |Cite
|
Sign up to set email alerts
|

Patient and central venous catheter related risk factors for blood stream infections in children receiving chemotherapy

Abstract: Both patient and CVC-related factors are associated with higher risk of BSI in children receiving chemotherapy. The results of this study could be used in developing studies aiming to reduce the rate of BSIs in children with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 25 publications
(32 reference statements)
4
38
1
Order By: Relevance
“…Central line-associated bloodstream infections (CLABSIs), the majority related with the use of the central venous catheter (CVC) [6,7], are the most important complications in critical care [810] and in cancer settings [11,12]. In particular, in cancer settings, several risk factors have been identified for CLABSIs in patients who undergo chemotherapy such as, for example, a prolonged duration of catheterization, microbial colonization at the insertion site and of the catheter hub, and inadequate care/maintenance of the CVC after insertion [1315]. Therefore, improving the quality of the health care is a key priority, since reduction of CLABSIs may be achieved through efforts with adherence to appropriate preventive measures in line with evidence-based recommendations [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Central line-associated bloodstream infections (CLABSIs), the majority related with the use of the central venous catheter (CVC) [6,7], are the most important complications in critical care [810] and in cancer settings [11,12]. In particular, in cancer settings, several risk factors have been identified for CLABSIs in patients who undergo chemotherapy such as, for example, a prolonged duration of catheterization, microbial colonization at the insertion site and of the catheter hub, and inadequate care/maintenance of the CVC after insertion [1315]. Therefore, improving the quality of the health care is a key priority, since reduction of CLABSIs may be achieved through efforts with adherence to appropriate preventive measures in line with evidence-based recommendations [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In six studies (21,23,(25)(26)(27)(28) , the physician was mentioned as the most qualified professional for the in-…”
Section: Indication For Insertionmentioning
confidence: 99%
“…Yacobovich, (27) Rajan, (28) 2016 India Report the experience of inserting a PICC when, after its insertion, it was observed that the tip was located in the jugular vein but, after 24 hours, it had migrated to the superior vena cava.…”
Section: Narrative Review Pediatric Surgeonsmentioning
confidence: 99%
See 2 more Smart Citations